Pre treatment by the crude and the n-hexane extract of Nigella sativa Linn. (Kalajira) alleviates diabetes mellitus (Bangladesh Journal of Medical Science, 2009)
Methodology: Effect of pretreatment by crude and n-Hexane extract of Nigella (10mg/kg body wt./day for 21 days) on streptozotocin (STZ, 50 mg/kg body wt. single dose i.p.) administered rats were observed in the present study. Biochemical parameters (Serum glucose, serum TG, serum cholesterol, pancreatic GSH) were compiled together with pancreatic histology. Results: Both the crude and the n-Hexane extract of Nigella pre-treated diabetic rats had demonstrated significant (P